2012
DOI: 10.1111/j.1538-7836.2012.04859.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of dabigatran anticoagulation by prothrombin complex concentrate (Beriplex P/N) in a rabbit model

Abstract: Summary.  Background:  One limitation of the direct thrombin inhibitor dabigatran is the lack of specific antidotes that allow acute bleeding events to be managed or urgent interventional procedures performed. Prothrombin complex concentrates (PCCs) have served as a standard treatment for the reversal of coumarin anticoagulation. Objectives:  This study was designed to determine in an animal model whether a PCC (Beriplex P/N) can effectively reverse the effects of dabigatran. An additional objective was to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(141 citation statements)
references
References 29 publications
5
136
0
Order By: Relevance
“…In experimental studies, diminished bleeding times have been observed in the absence of measurable parameter changes after PCC administration. 12,25 In our third experimental series, the application of PCC 30 minutes after TBI for anticoagulation reversal did not prevent the development of larger bleeding volumes in some of the mice with excess dabigatran levels as compared with saline injections. Apart from an incomplete anticoagulation reversal, another explanation might be that the PCC injection occurred at a time that was too late to substantially change the hemorrhage volume after 24 hours.…”
Section: Discussionmentioning
confidence: 69%
“…In experimental studies, diminished bleeding times have been observed in the absence of measurable parameter changes after PCC administration. 12,25 In our third experimental series, the application of PCC 30 minutes after TBI for anticoagulation reversal did not prevent the development of larger bleeding volumes in some of the mice with excess dabigatran levels as compared with saline injections. Apart from an incomplete anticoagulation reversal, another explanation might be that the PCC injection occurred at a time that was too late to substantially change the hemorrhage volume after 24 hours.…”
Section: Discussionmentioning
confidence: 69%
“…Human studies (dabigatrantreated healthy volunteers) PCC No reduction in blood loss after tail transection in mice [44] Reduced intracranial hematoma expansion and 24-hr mortality in mice [45] Reduced blood loss following kidney incision in rabbits [46] Reduced bleeding time, but not coagulation tests in rat tail transection model [18] Corrected some TG indices [25] Corrected PT, aPTT, TT and some TG indices [13] No correction of Hemoclot assay [13] No correction of aPTT, ECT, TT [9] aPCC No reduction in blood loss after tail transection in mice [44] Reduced bleeding time, but not coagulation tests in rat tail transection model [18] Corrected some TG indices [25] Corrected PT, aPTT and some TG indices [13] [23],…”
Section: Reversal Strategymentioning
confidence: 99%
“…28 In contrast, a study of dabigatran-associated bleeding in a rabbit model showed that treatment with the 4-factor PCC reduced blood loss and improved bleeding time. 29 Abbreviations: FEIBA, factor eight inhibitor bypass activity; FFP, fresh frozen plasma; PCC, prothrombin complex concentrate; rFVIIa, recombinant factor VIIa. a The use of FFP, platelets, or cryoprecipitate may be indicated owing to blood loss, but these therapies would not be expected to be helpful as monotherapy in the reversal of the novel oral anticoagulants.…”
Section: Dabigatran Etexilatementioning
confidence: 99%